Lateral Attitude Change. (August 2015) - Glaser, Tina; Dickel, Nina; Liersch, Benjamin; Rees, Jonas; Süssenbach, Philipp; Bohner, Gerd
The authors propose a framework distinguishing two types of lateral attitude change (LAC): (a) generalization effects, where attitude change toward a focal object transfers to related objects, and (b) displacement effects, where only related attitudes change but the focal attitude does not change. They bring together examples of LAC from various domains of research, outline the conditions and underlying processes of each type of LAC, and develop a theoretical framework that enables researchers to study LAC more systematically in the future. Compared with established theories of attitude change, the LAC framework focuses on lateral instead of focal attitude change and encompasses both generalization and displacement. Novel predictions and designs for studying LAC are presented.